Online microbiology interactive e-learning (OMIeL) - Azmilumur, Muhammad Anuarruddin; Hamid, Muhammad Syafiq Aizat; Harun, Muhammad Alif Syuqrie; Mohd Sayuti, Mohamad Azzam; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Online Microbiology Interactive e-Learning (OMIeL) in an interactive web-based learning of Microbiology designed for undergraduates students studying microbiology related courses. OMIeL is aimed to develop self-directed learners, instill interest and passion towards Microbiology. At the same time, students are exposed to self-paced learning environment together with 21st Century skills.